Experimental investigation of the thermal and electrical performance of the heat pipe BIPV/T system with metal wires. (15th May 2016) - Wang, Zhangyuan; Qiu, Feng; Yang, Wansheng; Zhao, Xudong; Mei, Sheng
Highlights: Proposing a novel heat pipe BIPV/T system. Conducting experiments to investigate the performance of the system. Establishing the relation between the system performance and operating parameters. Abstract: Heat pipe building integrated photovoltaic/thermal system (heat pipe BIPV/T system) can produce both the electrical and thermal energies at the same time, which have been paid enormous attentions since the energy crisis in the 1970s. In this paper, the heat pipe BIPV/T system with the metal wires filling into the space between the finned heat pipes and insulation has been proposed, which will be expected to enhance the heat transfer and improve the electrical generation of the system. To investigate the thermal performance of the system, the variations of the temperatures, e.g., flat-plate glass cover, PV panel, filling space, heat pipe, and tank water, as well as the ambient temperature, were measured, and the system's thermal efficiency was calculated and studied for different simulated solar radiations and water flow rates. It was found that the temperatures of the flat-plate glass cover, PV panels, filling space, and heat pipe presented the similar variation pattern when the ambient temperature was stable. The tank water temperature could reach the maximum of 53.83 °C when the simulated solar radiation was at 900 W/m 2 and the water flow rate was at 200 l/h. The linear relation between the system efficiency and ( Tmean − Tamb )/ I had been setup. The maximum thermal efficiency was found at 44.04% with the simulated solar radiation of 300 W/m 2 and water flow rate of 200 l/h, and 7.9% for the maximum electrical efficiency. Compared with the traditional systems of the previous research, the proposed system performed well with additional features, e.g., low cost, waste materials recycling. This research will be helpful in indicating the potential research area of the low-carbon-emission and energy-saving technology for the researchers overseas and domestic.